Increase Students' Learning Interest in Islamic Education Material Using Methods Snowball Throwing In Class III: Meningkatkan Minat Belajar Siswa Pada Materi PAI Menggunakan Metode Snowball Throwing Pada Kelas III - siti ariana (International Journal of Technology Vocational Education and Training, 2020)
This research is motivated by the learning outcomes of students in learning (IPA) there are still many who have not reached the completeness criteria, because the students' attitudes are less focused when the teacher explains the material, they are cool alone with their fellow students so the learning process becomes less effective. In addition students are not able to remember the material that has been learned and the students' lack of understanding of the concept of the material being taught. Therefore, it is hoped that using a model with pictures will help the learning process. This is because students find it easier to remember pictorial material. Therefore we need an attractive and effective learning model that can improve students' memory and understanding of concepts so that they can have a positive impact on student learning outcomes.